2019
DOI: 10.1136/bmjopen-2018-026764
|View full text |Cite
|
Sign up to set email alerts
|

Scanning the horizon: a systematic literature review of methodologies

Abstract: ObjectivesSociety is confronted with the rapid emergence of innovation in science and technology. To manage this, horizon scanning is being adopted globally to identify, assess and prioritise innovations and trends at an early stage of their development. This enables decision-makers to be better informed and to prepare for change. The aim of this paper is to systematically identify and evaluate horizon scanning methodologies employed in the healthcare and biomedical fields.MethodsA systematic literature review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 51 publications
0
74
0
Order By: Relevance
“…Regarding practical benefits of podcast mining we may conclude that using podcasts as an additional source in HS could help decision makers to maintain a broad view and receive early warning of signals. HS has been used for many years in business enterprises and public bodies across different sectors to support policy and research planning (Hines et al, 2019). For some time, open-source materials (such as social media) are becoming increasingly important for organizations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding practical benefits of podcast mining we may conclude that using podcasts as an additional source in HS could help decision makers to maintain a broad view and receive early warning of signals. HS has been used for many years in business enterprises and public bodies across different sectors to support policy and research planning (Hines et al, 2019). For some time, open-source materials (such as social media) are becoming increasingly important for organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating podcast mining in systematic or ad hoc HS processes could be better facilitated by improved automation. Development of artificial intelligence may enable possibly soon complex filtration and self-assessment which will significantly improve HS and ultimately decision making processes (Hines et al, 2019). In future, advanced text analytics could enhance capturing subjective opinions and uncover areas of disagreement or, on the contrary, fascination in podcasts and provide indication for e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We also rely on other sources commonly referenced by overseas HSSs, like trial registries, scientific journals and commercial developer websites (Table 1) (3;7). In addition, reports from overseas horizon scanning agencies, information from informal sources like research institutions, technology transfer offices, and print, electronic or social media channels may provide useful information (8). Eventually, ACE may emulate the approach adopted by some EuroScan member agencies and tap on clinical experts for their domain expertise to identify new and emerging technologies, especially those with a shorter innovation cycle or higher rate of diffusion (9).…”
Section: The Ace Horizon Scanning Systemmentioning
confidence: 99%
“…The ICMRA Innovation concept note 3 describes horizon-scanning as a broad-reaching information-gathering and monitoring activity to anticipate emerging products and technologies and potentially disruptive research avenues. Traditionally, horizon-scanning has been predominantly conducted in Europe for policy-making, scientific research funding, and health care budgeting purposes, by surveying a variety of sources — such as the Internet, government, international organisations and companies, databases, and journals — using the Delphi method, for example 4 5 . Recently, the European Commission(EC) has published some reports including “Weak signals in Science and Technologies 2019 Report based on Tools for Innovation Monitoring (TIM) 6 , which uses text mining and keywords in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…Hines et al reported that, in the medical and health care field, the majority of horizon-scanning methods used were manual or semiautomated, with relatively few automated aspects; this may be resolved in the not-too-distant future via the rapidly evolving fields of machine learning and artificial intelligence 5 .…”
Section: Introductionmentioning
confidence: 99%